2017
DOI: 10.1590/0047-2085000000154
|View full text |Cite
|
Sign up to set email alerts
|

Self-injury and suicide attempt among the elderly population in the city of São Paulo

Abstract: Objective: In this perspective, the present research aims to describe the reports of self-injury and suicide attempt among the elderly population living in the city of São Paulo. Methods: This is a descriptive, quantitative approach based on Violence and Accidents Surveillance Information System (SIVVA) of the city of São Paulo. In the selection of notifications, it was included the ones related to self-injury and attempted suicide against men and women, with age group between 60 and over, from January to Dece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 16 publications
0
6
0
5
Order By: Relevance
“…The remaining 0.2% ( n = 110) of participants used multiple methods to self-harm. The majority of studies reporting self-harm methods were in hospital-based settings, with the exception of four studies 32 , 47 , 57 , 58 that also reported community-based data. However, similar trends regarding self-harm methods used were reported across the different study settings as reported in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The remaining 0.2% ( n = 110) of participants used multiple methods to self-harm. The majority of studies reporting self-harm methods were in hospital-based settings, with the exception of four studies 32 , 47 , 57 , 58 that also reported community-based data. However, similar trends regarding self-harm methods used were reported across the different study settings as reported in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The remaining studies were conducted in other healthcare facilities (e.g. general hospitals, general practice, private clinics) ( n = 2), 57 , 58 community mental health services ( n = 2), 32 , 50 a national surveillance system which includes presentations from hospitals and primary care 47 and a national household survey 56 . Study length varied from 8 months to 26 years.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations